Energy supplementation level, live weight gain and behaviour of growing beef cattle grazing native pasture - Soca, P. M.; Cabrera, M. R.; Bruni, M. A. (Agrociencia Uruguay, 2007)
The effect of the supplementation level (S) on live weight gain (LWG) and grazing behavior of growing cattle grazing natural pasture was evaluated. During the year 1, eighteen growing cattle of 257 ± 14 kg live weight (LW) were assigned to S: S0.6 = 0.6; S1.0 = 1.0; S1.4 = 1.4 kg of concentrate/100 kg LW. In the year 2 twenty-four animals of 200 ± 20 kg of LW were assigned to S, S0. 2 = 0.2; S0.6 = 0.6; S1.0 = 1 and S1.4 = 1.4 kg of concentrate/100 kg LW. The animals grazed between 17:00 and 7:00 h. The live weigh (LW) was registered every 15 days, and the percentage of the time dedicated to grazing (GT), rumia (RT), rest and biting rate (Br). The LWG to year1 was of 0.52; 0.62 and 0.73 kg/day for S0.6; S1.0; S1.4 respectively and different S0.6; of S1.0 and S1.4 (P<0.05). > <0.05). In the year 2 it was 0.56; 0.57; 0.69; 0.81 kg/day for S, where S0.2 and S0.6 differed from S1.4 (P<0.05). .By each percentage unit of increment in S, LWG improved 0.262 and 0.218 kg (P<0.05) > <0.05) for the first and second year. S did not affect GT and Br and allowed improving the weight gain by animal and unit of surface. The carrying capacity maintained of 6 (year 1) and 10 (year 2) growing cattle of 250 kg of LW per hectare justified the use of the summer energy supplementation in cattle production systems of Uruguay attractive.